2018
DOI: 10.3390/nu10010040
|View full text |Cite
|
Sign up to set email alerts
|

Soy Consumption and the Risk of Prostate Cancer: An Updated Systematic Review and Meta-Analysis

Abstract: Prostate cancer (PCa) is the second most commonly diagnosed cancer in men, accounting for 15% of all cancers in men worldwide. Asian populations consume soy foods as part of a regular diet, which may contribute to the lower PCa incidence observed in these countries. This meta-analysis provides a comprehensive updated analysis that builds on previously published meta-analyses, demonstrating that soy foods and their isoflavones (genistein and daidzein) are associated with a lower risk of prostate carcinogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
2
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 69 publications
5
82
2
7
Order By: Relevance
“…High intake of soy was related to a reduced cancer risk of ovarian, prostate, gastric, colorectal, lung, and breast . Considering the different types of soy, high consumption of non‐fermented soy (tofu, soy protein, and soy milk) was related to a reduced risk of gastric cancer .…”
Section: Resultsmentioning
confidence: 99%
“…High intake of soy was related to a reduced cancer risk of ovarian, prostate, gastric, colorectal, lung, and breast . Considering the different types of soy, high consumption of non‐fermented soy (tofu, soy protein, and soy milk) was related to a reduced risk of gastric cancer .…”
Section: Resultsmentioning
confidence: 99%
“…Soy isoflavones and phytoestrogens genistein and daidzein were shown to reduce contractile dysfunction of cardiomyocytes induced by glucose toxicity, inhibit cardiovascular collagen accumulation, and reduce ischemic cardiomyopathy (Hintz and Ren 2004;Li and Zhang 2017;Mizushige et al 2007). Soy isoflavones also have anti-cancer properties as shown by reduced prevalence of cancer in populations regularly consuming soy rich diet possibly through early stimulation of cell differentiation (Applegate et al 2018). A recent report on safety evaluation of isoflavones based on in vivo studies to date found that overall, the evidence is inconclusive regarding adverse effects of long term isoflavone consumption (Huser et al 2018).…”
Section: But Res Binding Could Results Inmentioning
confidence: 99%
“…Table I summarizes studies on soy isoflavones and prostate cancer (101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112)(113)(114). Systematic reviews of double-blind placebo-controlled randomized clinical trials (15,(115)(116)(117) have summarized current human data that provide evidence for several anti-cancer properties of dietary supplements, including isoflavones, in reference to prostate cancer. Certain studies have indicated that the administration of isoflavone supplements does not change PSA concentrations, but not all studies come to this conclusion.…”
Section: Isoflavones As Ar Modulators: In Vitro and In Vivo Studies Amentioning
confidence: 99%
“…Furthermore, findings from epidemiological studies on the association between soy isoflavones and prostate cancer risk are incomplete and sometimes contradictory. The latest meta-analysis of 30 articles, comprising 15 case-control, 8 cohort and 7 nested case-control studies (266,699 total number of study participants and 21,612 patients), as performed by Applegate et al (15), demonstrated that total soy consumption is associated with a reduction of prostate cancer risk. The current review will summarize the existing knowledge and hypotheses concerning the mechanisms of soy isoflavones action on the AR signaling pathway in prostate cancer development.…”
Section: Introductionmentioning
confidence: 99%